Packed cell volume evaluation of the systems for self-monitoring of blood glucose GL50 evo and GL 44 following DIN EN ISO 15197: 2015. Issue 3 (2020) - Salzsieder, E; Puchert, A; , Ernst-Joachim Freyse; Berg, S
No abstract available